ELIPSIS DAN PRONOMINA DEMONSTRATIF PADA WACANA SOAL DOKKAI SETINGKAT NIHONGO NOURYOKU SHIKEN LEVEL 3 (N3) - Shinta Apriani; Arza Aibonotika; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The research discussed ellipsis and demonstrative pronouns on material test of reading comphereshion of Japanese Language Proficiency Test N3. This research is a qualitative descriptive research using Halliday and Hasan (1976) about Ellipsis and demonstrative pronoun as guidelines. In this source, ellipsis rarely appears, where the demonstrative pronouns appears more. Based on ten discourse of dokkai there are three categories of ellipsis namely ellipsis noun, verb ellipsis or form of word already mentioned, and ellipsis clause. In this study also obtained three types of demonstrative pronouns like pronominal demonstrative, adnominal adjective and adverb. From 35 data there are 5 demonstrative pronouns referring to katafora, whereas 30 data refer anaphorically.Key Words : demonstrative pronouns, dokkai, ellipsis, nihongo nouryoku shiken